Fixed Point Theorems for Generalized \((α,ψ)\)-Expansive Mappings in Generalized Metric Spaces - Kumar, Manoj; Araci, Serkan; Kumam, Poom (Communications in Mathematics and Applications, 2016)
The aim of this paper is to introduce new notion of generalized \((α,ψ)\)-expansive mappings in generalized metric spaces and to study the existence of a fixed point for the mappings in this space. Our new notion complements the concept of generalized \((α,ψ)\)-contractions on generalized metric spaces introduced recently by Aydi et al. (Journal of Inequalities and Applications 2014, 229 (2014)). The presented theorems extend, generalize and improve many existing results in the literature.